Pengaruh Kode Etik Aparat Pengawasan Intern Pemerintah (Apip) Dan Pengalaman Kerja Auditor Internal Terhadap Kualitas Audit - Ayem, Sri; Jehadi, Didimus (Jurnal Akuntansi dan Governance Andalas, 2019)
This study aims to determine the effect of integrity, objectivity, confidentiality, competence and work experience on the audit quality of internal auditors in the DIY Representative BPKP, both partially and simultaneously. This study uses primary data obtained from the distribution of questionnaires to respondents. The population in this study were all functional internal auditor officials at the BPKP DIY Representative, with the sampling technique using nonprobability sampling, namely purposive sampling. Purposive sampling is done by taking samples from several populations based on certain criteria. The relationship or influence between variables is explained by using multiple linear regression analysis and hypothesis testing (t test). The results showed that the integrity variable had no effect on audit quality, the objectivity variable had a positive effect on audit quality, the confidentiality variable had a positive effect on audit quality, the competency variable did not affect audit quality and the work experience variable had a positive effect on audit quality and simultaneously showed that the integrity variable , objectivity, confidentiality, competence, and work experience have a significant effect on audit quality.